Boron Nitride Nanotube Addition Enhances the Crystallinity and Cytocompatibility of PVDF-TrFE - Poudel, Anup; Fernandez, Marc A.; Tofail, Syed A. M.; Biggs, Manus J. P. (Frontiers in Chemistry, 2019)
Analysis of the cellular response to piezoelectric materials has been driven by recent development in externally and patient-powered implantable devices. In particular, polyvinylidene fluoride and the trifluoroethylene co-polymer (PVDF-TrFE) have been identified as promising piezo and ferroelectric materials with applications in energy harvesting and biosensor devices. Critically, the modulation of the structural and crystalline properties of PVDF-TrFE through annealing processes and the addition of particulate or fibrous fillers has been shown to impart significant effects on the materials electromechanical properties. In this study, PVDF-TrFE boron-nitride nanotube composites were evaluated by modulated differential scanning calorimetry to assess the effects of boron nitride nanotube addition and thermal annealing on the composite structure and crystal behaviour. An increased beta crystal formation (f(β)= 0.71) was observed following PVDF-TrFE annealing at the first crystallization temperature of 120˚C. In addition, the inclusion of boron-nitrite nanotubes increased the crystal formation behaviour (f(β)= 0.76) and the mechanical properties of the material. Finally, it was observed that the inclusion of boron nitride nanotube enhanced the adherence and proliferation of human tenocyte cells cultured on thin-film PVDF-TrFE/ boron-nitrite nanotube composites in vitro.